2021
DOI: 10.1111/cod.13910
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of occupational contact dermatitis in Denmark between 2007 and 2018: A population‐based study

Abstract: Background: Recent population-based studies on the incidence rates (IRs) of occupational contact dermatitis (OCD) are sparse. Objectives: To determine the IRs of OCD and development thereof between 2007 and 2018 in known risk occupations. Methods: Data on all recognized cases of OCD were used to calculate IRs as the number of recognized OCD cases per 10 000 workers per year. Asymptotic chisquare test was used to compare the IRs between 2007-2012 and 2013-2018. Results:The median age at notification of OCD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…We also found men to have a statistically significantly higher OR for having OACD. This corresponds to earlier studies, that have found that males have a higher prevalence of OACD compared to females because of exposures related to the metal-working industry and work tools, among others, 4,19 which can explain this gender discrepancy.…”
Section: Statements On Health Care Systemsupporting
confidence: 91%
“…We also found men to have a statistically significantly higher OR for having OACD. This corresponds to earlier studies, that have found that males have a higher prevalence of OACD compared to females because of exposures related to the metal-working industry and work tools, among others, 4,19 which can explain this gender discrepancy.…”
Section: Statements On Health Care Systemsupporting
confidence: 91%
“…Application of the factor of 0.1 is also consistent with the previous risk assessment considering the ratio of skin rinse to MEL for 3 other hair dyes 9 . Second, a factor of 10 was used to account for the prolonged exposure to wet work 22 associated with an increased likelihood of impaired skin barrier integrity and of ACD due to concomitant exposure to irritants and allergens 28–30 . Third, the resulting values were divided by 100 cm 2 representing the surface area of the hairdressers' hands/fingers that is directly exposed to the freshly colored hair during cutting, styling, and/or blow-drying, as previously described 9 .…”
Section: Discussionmentioning
confidence: 90%
“…A recent systematic review 14 of HE in the general population, found no decrease in the lifetime prevalence when comparing studies published before and after 2007, suggesting that the decreased career prevalence observed in our study not being due to general factors protecting against HE in the general population. Additionally, a recent study 15 found a decrease in the IR of recognized OHE in Danish hairdressers from 2012 onwards (IRR 0.64), while no simultaneous decrease were seen for other wet‐work occupations, further suggesting that the decreased risk of OHE if trained after implementation of the skin protection program likely being due to an increase in compliance with skin protective measures.…”
Section: Discussionmentioning
confidence: 93%